Metodologi Agile Scrum Dalam Peningkatan Efisiensi Tim Pengembangan Aplikasi Mobile - Ansari (CV. SINAR HOWUHOWU, 2025)
This study examines the implementation of the Agile Scrum Methodology in improving the efficiency of a mobile application development team. The research focuses on analyzing how the Scrum framework, with its iterative cycles called Sprints, impacts both quantitative aspects such as development velocity and qualitative aspects like team collaboration and product quality. The research method used is a qualitative approach with a case study, involving observation, interviews, and document analysis of Scrum artifacts from a mobile application development team. The findings indicate that the adoption of Scrum significantly enhanced the team's efficiency. Dividing the project into Sprints allowed the team to maintain focus, reduce delays, and consistently deliver new features faster. Daily Scrum was proven effective in facilitating communication and problem-solving, while Sprint Review and Retrospective played a crucial role in ensuring user feedback was integrated early and fostering continuous improvement. Although initial challenges in adapting to new roles and processes were found, the benefits gained from improved collaboration, product quality, and development speed far outweighed them. This study concludes that Scrum is a highly relevant and effective methodology for mobile application development teams in facing the dynamics of a fast-paced market.